Solution of the problems of metal heating control on the basis of the magistral asymptotic optimization method - V. I. Timoshpolsky; S. M. Kozlov; V. B. Kovalevsky; I. A. Trusova; V. V. Filippov (Литьë и металлургия)
The article generalizes main results of use of magistral optimization method for solving problem of effective conditions of steel heating development.